Castilian Days - Hay, John, 1838-1905 (Salt Lake City, UT : Project Gutenberg, 2005)
"Castilian Days" by John Hay is a historical account written in the early 20th century. The book serves as a vivid exploration of Spanish culture, society, and life during a transformative period around the late 19th century. Hay intricately describes various aspects of life in Spain, particularly focusing on Madrid, its customs, traditions, and the influences shaping its character. At the start of the book, the author provides rich and detailed observations about the city of Madrid, portraying it as a capital shaped heavily by historical forces rather than geographical advantages. Hay contrasts Madrid with other European capitals, emphasizing its unique mixture of cultures and the eclectic contributions from different regions in Spain. He highlights the complexities of Spanish society, addressing elements like the traditional charm of family gatherings, the domestication of sentiments, and the lingering vestiges of history that influence contemporary life. The opening lays a foundation for a deeper analysis of Spanish life, touching on social customs, political realities, and the interplay between modernity and tradition. (This is an automatically generated summary.)
Madrid al fresco -- Spanish living and dying -- Influence of tradition in Spanish life -- Tauromachy -- Red-letter days -- An hour with the painters -- A castle in the air -- The city of the Visigoths [Toledo] -- The Escorial -- A miracle play -- The cradle and the grave of Cervantes.
Release date is 2005-02-01
Produced by Eric Eldred and David Widger
Keywords: Spain -- Description and travel; Spain -- Social life and customs